Neonatal hypoxic ischemic encephalopathy increases acute kidney injury urinary biomarkers in a rat model. Issue 24 (21st December 2022) - Groves, Angela M.; Johnston, Carl J.; Beutner, Gisela G.; Dahlstrom, Jane E.; Koina, Mark; O'Reilly, Michael A.; Porter, George; Brophy, Patrick D.; Kent, Alison L.
Abstract: Hypoxic ischemic encephalopathy (HIE) is associated with acute kidney injury (AKI) in neonates with birth asphyxia. This study aimed to utilize urinary biomarkers to characterize AKI in an established neonatal rat model of HIE. Day 7 Sprague–Dawley rat pups underwent HIE using the Rice–Vannucci model (unilateral carotid ligation followed by 120 mins of 8% oxygen). Controls included no surgery and sham surgery. Weights and urine for biomarkers (NGAL, osteopontin, KIM‐1, albumin) were collected the day prior, daily for 3 days post‐intervention, and at sacrifice day 14. Kidneys and brains were processed for histology. HIE pups displayed histological evidence of kidney injury including damage to the proximal tubules, consistent with resolving acute tubular necrosis, and had significantly elevated urinary levels of NGAL and albumin compared to sham or controls 1‐day post‐insult that elevated for 3 days. KIM‐1 significantly increased for 2 days post‐HIE. HIE did not significantly alter osteopontin levels. Seven days post‐start of experiment, controls were 81.2% above starting weight compared to 52.1% in HIE pups. NGAL and albumin levels inversely correlated with body weight following HIE injury. The AKI produced by the Rice–Vannucci HIE model is detectable by urinary biomarkers, which can be used for future studies of treatments to reduce kidney injury. Abstract : Although animal models of brain injury resulting from HIE are well established, the kidney injury that occurs is not well studied. This study aims to characterize AKI in an established rat model of HIE and track injury progression using sensitive urinary biomarkers. This provides an experimental approach utilizable for testing effectiveness of therapies that treat AKI.